Study of the Level of Gene Expression of the GLUT2 Glucose Vector in the Small Intestine of the Meat Broiler and its Relationship to Productive Traits - Anwar Hammood Obaid Al-Omar (University of Thi-Qar Journal of agricultural research, 2022)
The study was conducted in the field of animal production of the Agricultural Research Station / College of Agriculture and the Marshes / Dhi Qar University for the period from 10/11/2021 to 25/ 2/ 2022. Laboratory tests of the samples were carried out in the Molecular Genetics Laboratory of the College of Dentistry / Dhi Qar University, for the purpose of knowing the gene expression of the SLC2A2 gene encoding the glucose transporter GLUT2 and the abundance of its mRNA transcripts in different regions of the small intestine of broilers when fed at different levels of energy and to study the relationship of that abundance to some productive traits.In this study, 135 non-naturalized of meat broiler (breed 308 Ross) were used. The broiler were randomly distributed to three experimental treatments, with three replicates for each group (15 chicks/repeat), used the adlibitum free feeding system for the duration of the experiment, which lasted (35) days. The study included three levels of energy, where the first treatment was a control diet, which represented 3065 and 3133 kilocalories/kg for the primer and final diet, respectively, as for the second treatment, it contained a high level of energy 3200 kilocalories/kg and 3297 kilocalories/kg for the primer and final diets, respectively, the third treatment contained a low level of energy 2769 kilocalories/kg and 2802 kilocalories/kg for primer and growth diets, respectively. The results of the study showed the following:-The possibility of amplifying the studied gene and knowing its abundance and according to the primers used.The highest level of mRNA transcription of the GLUT2 gene in the small intestine of males was in the jejunum region (9.41) at a representative energy level of 3297 kilocalories/kg, as for the duodenum, the expression of GLUT2 gene was lower than in the jejunum (0.535), the GLUT2 gene expression in males was slightly more than in females in the ileum region (0.578) at a representative energy level of 3297 kcal/kg.Gene expression was positively and significantly associated with live weight, weight gain and feed consumption rates, but it was inversely related to the efficiency of food conversion in the jejunum and duodenal regions.The abundance of the glucose transporter GLUT2 gene increased with the increase in the energy level in the diet.Males gave a higher percentage of mRNA copies in all target organs compared to females.The activity of the gene responsible for the transfer of glucose can be modified through feeding and increasing energy levels and thus its reflection on the performance of birds.As for the productive traits, the differences were significant in the average live body weight and weight gain, as well as feed consumption compared with the control treatment, while the feed conversion efficiency did not show any significant differences.